Volume of my Valentine 3

Level 2

In the half heart curve x 2 + ( 5 y 4 x ) 2 = 1 x^2 + (\dfrac{5y}{4} - \sqrt{x})^2 = 1 above, A B \overline{\rm AB} goes from the positive y y intercept to the positive x x intercept and points A , B , C A,B,C encloses the region R R .

Let a \textbf{a} be a positive real number.

If the region R R of the half heart curve x 2 + ( 5 y 4 x ) 2 = 1 x^2 + (\dfrac{5y}{4} - \sqrt{x})^2 = 1 is revolved about the line x = a \textbf{x = a} the resulting volume is V R = 8 π 5 ( arcsin ( ϕ 1 ) + ( ϕ 1 ) 1 6 ( ϕ 1 ) 2 + 2 5 ( ϕ 1 ) 5 2 1 3 ) V_{R} = \dfrac{8\pi}{5}(\arcsin(\phi - 1) + (\phi - 1) - \dfrac{1}{6}(\phi - 1)^2 + \dfrac{2}{5}(\phi - 1)^{\dfrac{5}{2}} - \dfrac{1}{3}) , where ϕ \phi is the golden ratio.

Find the line x = a \textbf{x = a} . Express the answer as a \textbf{a} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Feb 20, 2018

For the x x intercept of y 1 = 4 5 ( x 1 x 2 ) y_{1} = \dfrac{4}{5} (\sqrt{x} - \sqrt{1 - x^2}) we obtain:

x 2 + x 1 = 0 x = 1 ± 5 2 x^2 + x - 1 = 0 \implies x = \dfrac{-1 \pm \sqrt{5}}{2} , since x = 1 + 5 2 = ϕ x = -\dfrac{1 + \sqrt{5}}{2} = -\phi results in a complex valued square root x = 5 1 2 \implies x = \dfrac{\sqrt{5} - 1}{2} is the x intercept of y 1 = 4 5 ( x 1 x 2 ) y_{1} = \dfrac{4}{5} (\sqrt{x} - \sqrt{1 - x^2}) .

The equation of the line passing thru A : ( 0 , 4 5 ) A: (0,\dfrac{4}{5}) and B : ( 5 1 2 , 0 ) B: (\dfrac{\sqrt{5} - 1}{2},0) is:

y = 4 5 ( 2 x 5 1 + 1 ) y = \dfrac{4}{5} (\dfrac{-2x}{\sqrt{5} - 1} + 1) \implies

V R = 8 π 5 0 5 1 2 V_{R} = \dfrac{8\pi}{5} \int_{0}^{\frac{\sqrt{5} - 1}{2}} ( a x ) ( 1 2 x 5 1 + 1 x 2 x ) ) d x = (a - x)(1 - \dfrac{2x}{\sqrt{5} - 1} + \sqrt{1 - x^2} - \sqrt{x})) dx = 8 π 5 0 5 1 2 ( a x ) 1 x 2 + ( a x ) 2 a x 5 1 + 2 x 2 5 1 a x + x 3 2 ) d x \dfrac{8\pi}{5} \int_{0}^{\frac{\sqrt{5} - 1}{2}} (a - x)\sqrt{1 - x^2} + (a - x) - \dfrac{2ax}{\sqrt{5} -1} + \dfrac{2x^2}{\sqrt{5} - 1} - a\sqrt{x} + x^{\frac{3}{2}}) dx

For x 1 x 2 d x \int x\sqrt{1 - x^2} dx

Let x = sin ( θ ) d x = cos ( θ ) ( a x ) 1 x 2 d x = x = \sin(\theta) \implies dx = \cos(\theta) \implies \int (a -x)\sqrt{1 - x^2} dx = a cos 2 ( θ ) d θ + ( cos ( θ ) ) 2 ( sin ( θ ) ) d θ = a\int \cos^2(\theta) d\theta + \int (\cos(\theta))^2 (-\sin(\theta)) d\theta = a 2 ( θ + sin ( θ ) cos ( θ ) ) + ( cos ( θ ) ) 3 3 \dfrac{a}{2}(\theta + \sin(\theta)\cos(\theta)) + \dfrac{(\cos(\theta))^3}{3}

Let β = 5 1 2 = ϕ 1 \beta = \dfrac{\sqrt{5} - 1}{2} = \phi - 1

0 β x 1 x 2 d x = a 2 arcsin ( β ) + a 2 ( β ) 3 2 + 1 3 ( β ) 3 2 1 3 \implies \int_{0}^{\beta} x\sqrt{1 - x^2} dx =\dfrac{a}{2}\arcsin(\beta) + \dfrac{a}{2}(\beta)^{\frac{3}{2}} + \dfrac{1}{3}(\beta)^{\frac{3}{2}} - \dfrac{1}{3} \implies

V R = 8 π 5 ( a 2 arcsin ( β ) + a 2 ( β ) 3 2 + 1 3 ( β ) 3 2 1 3 + V_{R} = \dfrac{8\pi}{5} (\dfrac{a}{2}\arcsin(\beta) + \dfrac{a}{2}(\beta)^{\frac{3}{2}} + \dfrac{1}{3}(\beta)^{\frac{3}{2}} - \dfrac{1}{3} + ( a x x 2 2 a x 2 5 1 (ax - \dfrac{x^2}{2} - \dfrac{ax^2}{\sqrt{5} - 1} + 2 3 ( 5 1 ) x 3 2 a 3 x 3 2 + 2 5 x 5 2 ) 0 β ) = \dfrac{2}{3(\sqrt{5} - 1)} x^3 - \dfrac{2a}{3}x^{\frac{3}{2}} + \dfrac{2}{5}x^{\frac{5}{2}})|_{0}^{\beta}) = 8 π 5 ( ( 1 2 arcsin ( β ) + 1 2 ( β ) 1 6 ( β ) 3 2 ) a + \dfrac{8\pi}{5}((\dfrac{1}{2}\arcsin(\beta) + \dfrac{1}{2}(\beta) - \dfrac{1}{6}(\beta)^{\frac{3}{2}})a + ( 1 3 ( β ) 3 2 1 6 ( β ) 2 + + 2 5 ( β ) 5 2 1 3 ) ) (\dfrac{1}{3}(\beta)^{\frac{3}{2}} - \dfrac{1}{6}(\beta)^2 + + \dfrac{2}{5}(\beta)^{\frac{5}{2}} - \dfrac{1}{3}))

V R = 8 π 5 ( arcsin ( β ) + β 1 6 ( β ) 2 + 2 5 ( β ) 5 2 1 3 ) V_{R} = \dfrac{8\pi}{5}(\arcsin(\beta) + \beta - \dfrac{1}{6}(\beta)^2 + \dfrac{2}{5}(\beta)^{\frac{5}{2}} - \dfrac{1}{3}) \implies

( 3 arcsin ( β ) + 3 β ( β ) 3 2 6 ) a = 3 arcsin ( β ) + 3 β ( β ) 3 2 3 a = 2 (\dfrac{3\arcsin(\beta) + 3\beta - (\beta)^{\frac{3}{2}}}{6})a = \dfrac{3\arcsin(\beta) + 3\beta - (\beta)^{\frac{3}{2}}}{3} \implies \boxed{a = 2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...